(untitled) (Revista de Ensino em Artes, Moda e Design, 2025)
ABSTRACT This research investigates the symbiotic relationship between the entertainment industry and the textile clothing market, with a focus on character costumes and their interaction with light, color, and the fashion world. This qualitative study is based on a review of publications from 2010 to 2023. The study demonstrates that visual entertainment has a significant impact on people’s emotions and social culture, creating a dynamic cycle of influence that stimulates the production and consumption of clothing. To explore this cycle economically, the textile industry has created licensed apparel, consisting of fashion collections inspired by entertainment characters duly protected by intellectual property rights. The contemplation of characters stimulates the demand for this type of clothing, which in Brazil has a market of 45 million diverse consumers willing to spend 40% above the national average on licensed products. Therefore, entertainment and fashion intertwine, fueling a constantly growing industry, highlighting the powerful relationship between art, emotion, fashion, and consumption. Keywords: Licensed apparel; Fashion; Entertainment.